(untitled) (LACCEI, 2024)
The contamination of water and soil by tannery waste in Arequipa, Peru, has become a problem due to the discharge of pollutants, especially chromium, into the drainage system, which may threaten the health of nearby human settlements. Therefore, the research aims to determine phytoremediation efficiency (using Eleocharis montevidensis, Scirpus americanus, and Eichhornia crassipes) in removing chromium from tannery effluents using artificial wetland systems that combine different plant species. Physicochemical parameters and plant responses were measured before and after treatment. The study demonstrated that chromium removal efficiency was 99.6% after seven days of treatment with the wetlands. Additionally, the concentration of hexavalent chromium did not exceed 0.02 ppm after treatment. It was observed that Scirpus acclimatized better to chromium stress and tannery effluent than Eleocharis, while the species Eichhornia did not show significant changes.